THU0704 A new assessment tool for ulnar drift in patients with rheumatoid arthritis using pathophysiological parameters of the metacarpophalangeal joint. (12th June 2018) - Toyama, S.; Oda, R.; Tokunaga, D.; Asada, M.; Kawahito, Y.; Fujiwara, H.; Kubo, T.
Abstract : Background: Ulnar drift (UD) in rheumatoid arthritis (RA) is the most common and difficult to manage deformity in the rheumatoid hand; it is reported that 44% of patients develop UD within the first 10 years. Nevertheless, the assessment of UD is challenging; the Fearnley classification method, first reported in 1951, is still used for evaluation. However, it is sometimes difficult to determine the best surgical procedure simply based on the Fearnley classification, which only evaluates reducibility. Therefore, we have been using both the Fearnley classification as a 'gold standard' and an original scoring method that enables us to easily treat the deteriorated condition contributing to UD. Objectives: To establish and verify a new assessment tool for UD in rheumatoid hand. Methods: We established an observational cohort of 67 patients (134 rheumatoid hands) beginning in 2004, among the RA outpatients who had any apparent finger deformity in either hand. Fifty-two patients (100 hands) had follow-up in 2009, and thirty-seven patients (63 hands) completed follow-up in 2015. For evaluation of UD, we used both the Fearnley classification as a 'gold standard' and an original scoring method which assesses four parameters of the metacarpophalangeal joint. Cluster analysis using UD parameters divided hands into groups. For functional assessment, we used the modified Kapandji index (MKI). The MKI enables us to assess unilateral hand functional mobility within a few minutes. Changes in UD over time, correlation of the Fearnley stage and cluster with MKI, and reliability of the parameters with clustering were analysed. Results: The 10 year follow-up rate was 55.2%, and UD increased and worsened over time (p<0.001). A dendrogram indicated five clusters would be appropriate. Twenty-six hands in total changed to a higher cluster number during the follow-up period. Both the Fearnley classification and cluster were associated with MKI significantly. Though the Fearnley classification showed a floor effect, our method related to function more linearly (R-squared: 0.42). Each parameter of our method showed statistical significance for the clusters by regression analysis. And the ratio of the partial regression coefficient of each parameter was around 1:1:3:2, so we calculated a 'cluster score' using a weighted score for each parameter. A regression analysis has shown a strong correlation (r=0.95, p<0.001); however, its scatter plot also suggested that it is difficult to classify the cluster using CS only. We found one type of hand in which bone destruction precedes the joint dislocation and one type in which joint dislocation progresses with little deviation during UD progression. It is considered that two patterns of pathological findings and included some suggested indications for operative therapy to recover disability due to UD. Conclusions: Our UD evaluation method is quite simple but is closely related to function. Additionally, it enables dividing UD hands into five stages. Thus, our assessment should be beneficial compared to the Fearnley classification in considering treatments of UD. Acknowledgements: The authors thank all the researchers involoved in this 10 year observational study. Disclosure of Interest: None declared